Clinical Effectiveness and Safety of Vedolizumab vs. Infliximab in Biologic-Naive Ulcerative Colitis Patients: A Brazilian Real-World Multicentric Observational Study - Ferreira, S. (2024)
Hosp Clin Ribeirao Preto, Med, Med Sch, Ribeirao Preto, Brazil